Principles and strategies of creative broadcasting program for Indonesian local TV: a descriptive study - Abdussalam, Surokim; Wahyudi, Muhtar (Penerbit Universiti Kebangsaan Malaysia, 2016)
Local TV programmes in Indonesia have grown rapidly along with the advent of local TV stations. The diversity of content in local TV broadcasting allows for more choices for viewers and these program offers more content variety. However, in order to make local TV programs more competitive with the international programmes, TV producers should be more strategic in developing their content. This study delved into the principles and strategies used by local TV in East Java using constructivist paradigm. Data was obtained through interviews, observation and focus group discussions (FGD). Results showed that local TV programmes can be developed professionally based on seven principles i.e. entertaining, educating, reality, proximity, interactive, youth, and sustainable. Meanwhile, strategy can be developed through creativity, empathetic, fanatism, community, sharing and participation, positioning, branding-color, scheduling, unique actor, local dialect, gifts, research, networking, and economy.